Cybersecurity: today's most pressing governance issue. Issue 3 (2nd September 2019) - Nolan, Christopher; Lawyer, Glenn; Dodd, Ryan Marshall
ABSTRACT: Cybersecurity is today's most pressing corporate governance issue, but one which Boards of Directors and senior management find challenging to manage. The concept of cyber hygiene can define stress tests which assess Cyber Value at Risk, helping companies manage cyber risk as other macro-level business risks. Cyber hygiene can be described as the frequency of cybersecurity related operational stoppages or disruptions and the time required to resolve these issues when they occur. Hygiene also includes cybersecurity yield, the efficiency of a company's security expenditure in relation to the Value at Risk. Cyber Value at Risk is a financial component of a benchmarking exercise necessary to determine cyber governance quality at an enterprise level. Cybersecurity poses significant financial risks to enterprise value, justifying its classification as a governance issue and management quality indicator. Including cybersecurity in the environment, social and governance framework prioritises the risk on board, senior management and investor agendas. Key regulatory oversight bodies increasingly require companies to manage cyber risk in a manner consistent with other macro-level business risks. Reporting on cybersecurity risk in financial terms enables the board and full executive management team to manage cyber like any strategic business risk.